Study design and methods of the Wells and Enteric disease Transmission (WET) Trial: a randomised controlled trial. Issue 3 (2nd March 2023) - Lee, Debbie; Denno, Donna; Tarr, Phillip; Wu, Jingwei; Stokdyk, Joel P; Borchardt, Mark; Murphy, Heather M
Abstract : Introduction: The burden of disease attributed to drinking water from private wells is not well characterised. The Wells and Enteric disease Transmission trial is the first randomised controlled trial to estimate the burden of disease that can be attributed to the consumption of untreated private well water. To estimate the attributable incidence of gastrointestinal illness (GI) associated with private well water, we will test if the household treatment of well water by ultraviolet light (active UV device) versus sham (inactive UV device) decreases the incidence of GI in children under 5 years of age. Methods and analysis: The trial will enrol (on a rolling basis) 908 families in Pennsylvania, USA, that rely on private wells and have a child 3 years old or younger. Participating families are randomised to either an active whole-house UV device or a sham device. During follow-up, families will respond to weekly text messages to report the presence of signs and symptoms of gastrointestinal or respiratory illness and will be directed to an illness questionnaire when signs/symptoms are present. These data will be used to compare the incidence of waterborne illness between the two study groups. A randomly selected subcohort submits untreated well water samples and biological specimens (stool and saliva) from the participating child in both the presence and absence of signs/symptoms. Samples are analysed for the presence of common waterborne pathogens (stool and water) or immunoconversion to these pathogens (saliva). Ethics: Approval has been obtained from Temple University's Institutional Review Board (Protocol 25665). The results of the trial will be published in peer-reviewed journals. Trial registration number: NCT04826991 .